METHODS AND SKILLS OF COMBINING TECHNOLOGICAL EDUCATION WITH PEDAGOGICAL SCIENCES - Salimboy Akromovich Boltaboev; Dilshod Baxtierovich Luxmanov (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides an overview of the requirements for future teachers of technological education to radically reform their professional pedagogical activities and increase their professional competence. Defines the main purpose of the formation of specialist competence by identifying the psychological and pedagogical conditions and developing a mechanism for monitoring and evaluating its quality.